Sparse CL-SRME using impulse response and source wavelet: Method and applications - Hashim, H. (European Association of Geoscientists and Engineers, EAGE, 2019)
We proposed a new approach for multiple removal using the CL-SRME method. Instead of directly updating the estimated primaries, we update the impulse response and the source wavelet together during inversion as both are used to defined the primaries estimate. Through imposing the sparsity constraint toward the update of the primary impulse, we can obtained the spiky primary impulse and reduce the time for its convergence. With an example from both synthetic and field data of Malay Basin, it shows that this new approach works on both shallow and complex geological area. One advantage of using the new approach is it were able to recover the primaries continuity which are often missing due to primaries-multiples overlap. The faster rate of convergence also proves that this new approach could be an alternative to EPSI or CL-SRME. Â© 2019 Asia Petroleum Geoscience Conference and Exhibition, APGCE 2019. All rights reserved.